Catalyst-free, direct electrochemical synthesis of annulated medium-sized lactams through C–C bond cleavage. Issue 4 (17th December 2019) - Xu, Zhongnan; Huang, Zhixing; Li, Yueheng; Kuniyil, Rositha; Zhang, Chao; Ackermann, Lutz; Ruan, Zhixiong
Abstract : Expanding ring under green electricity: The electrosynthetic approach enabled atom-economical synthesis of challenging medium-sized lactams through a unique remote amidyl migration under exceedingly mild, transition metal- and oxidant-free conditions. Abstract : A catalyst-free, direct electrochemical synthesis of synthetically challenging medium-sized lactams through C–C bond cleavage has been developed. In contrast to previous typical amidyl radical cyclization, this electrosynthetic approach enabled step-economical ring expansion through a unique remote amidyl migration under mild, metal- and external-oxidant-free conditions in a simple undivided cell. The strategy features unparalleled broad substrate scope with all ring sizes of (hetero)aryl-fused 8–11-membered rings and hetero atom-tethered rings, high yields, and good functional group tolerance. Our experimental and computational findings provided strong support for a SET-based reaction manifold.